Single-cell transcriptomics of acetaminophen-induced responses in human 2D and 3D liver microtissues - Brian Bwanya; Marcha C. T. Verheijen; Duncan Hauser; Theo M. de Kok; Danyel G. J. Jennen; Twan van den Beucken; Florian Caiment (Archives of Toxicology, 2026)
Drug-induced liver injury remains a major obstacle in pharmaceutical development and a leading cause of acute liver failure, underscoring the need for predictive and human-relevant in vitro models. Acetaminophen, a widely used analgesic with well-characterized dose-dependent hepatotoxicity, serves as a benchmark compound for evaluating liver toxicity mechanisms. Here, we applied single cell RNA sequencing to characterize cellular responses to acetaminophen exposure in two distinct liver cell culture formats: two-dimensional monolayers (2D) and three-dimensional (3D) spheroids composed of primary human hepatocytes, Kupffer cells, and liver endothelial cells. Cultures were exposed for 24 h to low (350 µM) and high (2687 µM) acetaminophen concentrations, with 2D cultures receiving only the low dose. Compared to 2D monolayers, 3D spheroids exhibited greater transcriptional diversity and elevated expression of ribosomal genes, indicative of enhanced metabolic and biosynthetic activity. Reactome pathway analysis revealed pronounced hypoxia-associated signaling in 3D cultures even under baseline conditions, likely due to restricted oxygen diffusion within spheroids. These hypoxia signatures were most prominent in endothelial cells. Upon acetaminophen exposure, hypoxic hepatocytes displayed elevated expression of cytochrome P450 enzymes, while conjugation enzymes involved in detoxification declined with increasing dose, suggesting compromised phase II metabolism under oxygen-limited conditions. Normoxic hepatocytes showed minimal transcriptional response. These results suggest a dynamic interplay between oxygen availability and acetaminophen metabolism, where oxygen tension influences metabolic activity, and drug metabolism in turn alters the hypoxic landscape. Our findings underscore the physiological relevance of 3D liver models and highlight the importance of spatial microenvironmental context for improving mechanistic insights into hepatotoxicity.

Synergy and interference in community interactions of fungal endophytes in the liverwort Marchantia polymorpha - Jessica Nelson; Duncan Hauser (Symbiosis, 2025)
Plant microbiomes are diverse communities of many microbial species. Growing evidence suggests that a complex network of interactions between members of the microbiome is necessary to maintain the health of host plants. Overall microbiome impacts can be difficult to predict and there is still much unknown about how taxonomic diversity links to function. All research on such dynamics so far has been limited to vascular plants, but the non-vascular bryophytes also have rich microbiomes and understanding these is a necessary component for understanding the evolution and ecology of plant microbiomes. This study takes advantage of the existing fungal endophyte culture collection for the model liverwort Marchantia polymorpha L. to begin expanding experiments on microbiome community interactions into bryophytes. This series of experiments reveals examples of synergy, interference, and priority effects in how fungal endophyte combinations impact M. polymorpha . These results constitute a foundation for the development of more complex synthetic community studies similar to those already existing for vascular plant models.

Comparing in vitro human liver models to in vivo human liver using RNA-Seq - Rajinder Gupta; Yannick Schrooders; Duncan Hauser; Marcel van Herwijnen; Wiebke Albrecht; Bas ter Braak; Tim Brecklinghaus; Jose V. Castell; Leroy Elenschneider; Sylvia Escher; Patrick Guye; Jan G. Hengstler; et al. (Archives of Toxicology, 2021)
The liver plays an important role in xenobiotic metabolism and represents a primary target for toxic substances. Many different in vitro cell models have been developed in the past decades. In this study, we used RNA-sequencing (RNA-Seq) to analyze the following human in vitro liver cell models in comparison to human liver tissue: cancer-derived cell lines (HepG2, HepaRG 3D), induced pluripotent stem cell-derived hepatocyte-like cells (iPSC-HLCs), cancerous human liver-derived assays (hPCLiS, human precision cut liver slices), non-cancerous human liver-derived assays (PHH, primary human hepatocytes) and 3D liver microtissues. First, using CellNet, we analyzed whether these liver in vitro cell models were indeed classified as liver, based on their baseline expression profile and gene regulatory networks (GRN). More comprehensive analyses using non-differentially expressed genes (non-DEGs) and differential transcript usage (DTU) were applied to assess the coverage for important liver pathways. Through different analyses, we noticed that 3D liver microtissues exhibited a high similarity with in vivo liver, in terms of CellNet (C/T score: 0.98), non-DEGs (10,363) and pathway coverage (highest for 19 out of 20 liver specific pathways shown) at the beginning of the incubation period (0 h) followed by a decrease during long-term incubation for 168 and 336 h. PHH also showed a high degree of similarity with human liver tissue and allowed stable conditions for a short-term cultivation period of 24 h. Using the same metrics, HepG2 cells illustrated the lowest similarity (C/T: 0.51, non-DEGs: 5623, and pathways coverage: least for 7 out of 20) with human liver tissue. The HepG2 are widely used in hepatotoxicity studies, however, due to their lower similarity, they should be used with caution. HepaRG models, iPSC-HLCs, and hPCLiS ranged clearly behind microtissues and PHH but showed higher similarity to human liver tissue than HepG2 cells. In conclusion, this study offers a resource of RNA-Seq data of several biological replicates of human liver cell models in vitro compared to human liver tissue.